Seismic Control of Tall Buildings Using Distributed Multiple Tuned Mass Dampers - Hamid Radmard Rahmani; Carsten Könke (Advances in Civil Engineering)
The vibration control of tall buildings during earthquake excitations is a challenging task because of their complex seismic behavior. This paper investigates the optimum placement and properties of the tuned mass dampers (TMDs) in tall buildings, which are employed to control the vibrations during earthquakes. An algorithm was developed to spend a limited mass either in a single TMD or in multiple TMDs and distribute it optimally over the height of the building. The nondominated sorting genetic algorithm II (NSGA-II) method was improved by adding multivariant genetic operators and utilized to simultaneously study the optimum design parameters of the TMDs and the optimum placement. The results showed that, under earthquake excitations with noticeable amplitude in higher modes, distributing TMDs over the height of the building is more effective in mitigating the vibrations compared to the use of a single TMD system. From the optimization, it was observed that the locations of the TMDs were related to the stories corresponding to the maximum modal displacements in the lower modes and the stories corresponding to the maximum modal displacements in the modes which were highly activated by the earthquake excitations. It was also noted that the frequency content of the earthquake has significant influence on the optimum location of the TMDs.